Importance of humanities in oral health curricula - Deangelillo, Cristina Alicia (Acta Bioethica, 2006)
In order to be authentic, education must be based on values, not only a training in practice and theoretical aspects. This implies that, for dentistry training as well, we must prepare persons who reflect upon the consequences of their actions. We must train not only technicians, but professionals with broad scientific knowledge in relation with personal values. The introduction of bioethics in oral health curricula is an essential measure.